1985
DOI: 10.1063/1.334552
|View full text |Cite
|
Sign up to set email alerts
|

Ion and electron mobilities in cryogenic liquids: Argon, nitrogen, methane, and ethane

Abstract: Ion mobilities at low fields have been measured over the entire liquid range in argon, nitrogen, and methane. Gas-phase values for argon and nitrogen are also given. Comparison of the ratio of electron to ion mobilities confirmed that the electron remains nearly free in argon and methane liquids but is an anion in liquid nitrogen. At T≲116 K, the product of viscosity and either cation or anion mobility is constant in liquid nitrogen under its vapor pressure. At T>118 K, an abrupt destabilization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…When the gas density increases, the mobilities decrease. In N2 gas, our K+(N) variation is in good agreement with the data of Gee and Freeman [7]. Moreover, the extrapolation at 2.5 x lo1' cm-3 (atmospheric pressure) of the The electrical characteristics of the current pulses (e.g.…”
Section: Nitrogen N[mol/c;m3]supporting
confidence: 83%
“…When the gas density increases, the mobilities decrease. In N2 gas, our K+(N) variation is in good agreement with the data of Gee and Freeman [7]. Moreover, the extrapolation at 2.5 x lo1' cm-3 (atmospheric pressure) of the The electrical characteristics of the current pulses (e.g.…”
Section: Nitrogen N[mol/c;m3]supporting
confidence: 83%
“…In liquefied argon, the mobility of positive charge carriers, deduced from the current (using eq. 3) is in agreement with ion mobility measured by a time of flight method by other authors [5,6] but lower by a factor 2 than Freeman's results [2]. The product of viscosity by cation mobility (qK+) is, as expected, constant at least up to T=T,-IO ( fig.…”
Section: Point Anodesupporting
confidence: 89%
“…This result can be used to estimate the cation radius according to: R=elGqK+, we obtained R=0.5 nm for T<140K. The decrease of qK+ near Tc was attributed to electrostriction which would increase the local density and thereby the local viscosity [ 2 ] . In gaseous argon, the charge carrier mobility decreases with density as N-' .…”
Section: Point Anodementioning
confidence: 98%
“…A recent ICARUS measurement suggested that µ i is consistent with 0.9 × 10 −3 cm 2 V −1 s −1 . MicroBooNE showed a reasonable agreement between the model prediction and the measured electric field [8] if a µ i of 1.5 × 10 −3 cm 2 V −1 s −1 , as reported in [10], is used. Equations ( 6) and ( 7) are a one-dimensional approximation that assumes symmetry in the y and z coordinates.…”
Section: Space Charge Effectsmentioning
confidence: 98%